2004
DOI: 10.1149/1.1690289
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ethoxylated α-Naphtholsulfonic Acid on Tin Electroplating at Iron Electrodes

Abstract: Effects of ethoxylated ␣-naphtholsulfonic acid ͑ENSA͒ on the initial stages of tin plating have been studied on iron electrodes in an acidic stannous sulfate solution containing phenolsulfonic acid as a supporting electrolyte using potentiodynamic polarization, electrochemical quartz crystal microbalance ͑EQCM͒, scanning probe microscopy ͑SPM͒, and electrochemical impedance spectroscopy techniques. The smallest exchange current density and a larger transfer coefficient are observed at a typical ENSA concentrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 23 publications
(34 reference statements)
0
22
0
Order By: Relevance
“…Table 2 shows examples of recent bath formulations. [7][8][9][10][11][12][13][14][15][16] Several recent investigations from our laboratory have been based on acidic electrolytes. Such baths contain sulphuric acid (molar mass: 98.1 g mol -1 ), methanesulfonic acid (molar mass:…”
Section: Recent Investigations Of Methanesulfonic Acid Electrolytes Fmentioning
confidence: 99%
See 1 more Smart Citation
“…Table 2 shows examples of recent bath formulations. [7][8][9][10][11][12][13][14][15][16] Several recent investigations from our laboratory have been based on acidic electrolytes. Such baths contain sulphuric acid (molar mass: 98.1 g mol -1 ), methanesulfonic acid (molar mass:…”
Section: Recent Investigations Of Methanesulfonic Acid Electrolytes Fmentioning
confidence: 99%
“…The presence of the naphtholsulfonic acid also slowed down the hydrogen evolution reaction and reduced the impact of tin dissolution. 11 The effect of gelatin on tin deposition from sulphuric acid has been studied in some detail. The potential for hydrogen evolution was shifted to more negative values; approximately 0.3 V in the presence of 2 g dm 3 gelatin and the limiting current density was lowered.…”
Section: Electrolyte Additives and Operating Parametersmentioning
confidence: 99%
“…Such additives can be non-ionic, anionic or cationic [4,5]. Table 1 shows recent examples of electrolyte conditions used to electrodeposit tin [6][7][8][9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Among them are grain refiners (e.g., aldehydes, thiourea, PEG decyl glucoside, gelatin, peptone) [4][5][6][7], brighteners (e.g., Triton X-100, formaldehyde) [5,8,9], levelling additives (e.g., sesame oil, aromatic carbonyl compounds) [10][11][12], and complexing compounds (e.g., citrate, gluconate, tartrate) [13][14][15][16] were examined. The influence of bath constituents on the course of the early stages of tin electrodeposition and the kinetics of Sn(II) ion reduction was also discussed in some papers [15][16][17][18][19][20][21], as it shows a great influence on the further growth of the metal layer. In turn, Sharma et al [22] showed that the morphology of tin deposits can also be modified by the proper selection of current density, duty cycle, and frequency during pulsed current electrodeposition.…”
Section: Introductionmentioning
confidence: 99%